An Integrative SWAT-Based and Epistemological Framework for Sustainable Management of the Alo-Molamahu SubWatershed, Gorontalo, Indonesia - Bontor L. Tobing; Mahludin A. Baruwadi; Hasim Hasim (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Sustainable watershed management requires decision-making frameworks that are both scientifically robust and socially legitimate. This study develops an integrative management model for the Alo-Molamahu Sub-Watershed, part of the Limboto Watershed in Gorontalo Province, Indonesia, by combining hydrological modeling, spatial analysis, and social–institutional assessment within an epistemological framework. A mixed-methods design was employed, integrating biophysical data derived from Geographic Information Systems (GIS) and the Soil and Water Assessment Tool (SWAT) with qualitative data obtained from interviews, questionnaires, and policy document analysis. Model calibration and validation using observed discharge data from River Flow Monitoring Stations demonstrate strong agreement between simulated and observed hydrological responses. The results indicate that land-use change on steep slopes and limited vegetation cover significantly increase runoff and sediment yield, while socio-economic pressures and weak policy instruments constrain effective conservation practices. Through systematic data triangulation, biophysical model outputs were interpreted alongside stakeholder perceptions and regulatory conditions to generate an evidence-based and adaptive watershed governance model. The study demonstrates that integrating validated hydrological simulations with social knowledge enhances both the scientific credibility and policy relevance of watershed management strategies. The proposed framework provides a replicable approach for sustainable management of complex socio-ecological watersheds in Indonesia and comparable contexts.